Peran Aktif Mahasiswa Kkn Dalam Menyajikan Materi Pembelajaran Dengan Menggunakan Metode Role Playing Untuk Menciptakan Kondisi Belajar Mengajar Yang Kondusif di Kelas 5 SDN Nagrak - Nurul Fauziah, Nela; Hurun'in, Salsabila; Assadulloh, Arif At Tarmidzi; Jumadi, ST., MCs. (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
This article examines the active role of university students participating in the Community Service Program (KKN) in delivering learning materials at SDN Nagrak using the role-playing method in the fifth-grade classroom. The role-playing method was chosen for its ability to be conducted outdoors, enhancing student interaction, creativity, and motivation. This research employs a qualitative approach with a case study involving observation, interviews, and documentation. The findings indicate that the role-playing method is effective in improving students' understanding of learning materials, as well as their activity levels, communication skills, creativity, and critical thinking abilities. Despite challenges in engaging shy students, the positive impacts of this method in both the short and long term are significant, making it a valuable alternative for learning in unconventional situations.